SOSIALISASI 3 DOSA PENDIDIKAN BAGI ANAK-ANAK DI DESA RAWANG PASAR IV - Nova Eliza Silaen; Dewi Astuti; Vanny Anzarina; Putri Tamara; Aulia Intan Khairani; Nurul Syakinah; Sri Rezki Febriani (Smart Education, 2024)
The aim of this service activity is to provide an understanding of the importance of the three educational sins that influence the character development of children in Rawang Pasar IV Village. The activity method used is the lecture method or delivering material directly to the children in the village. This socialization aims to instill positive character values in children so that problems such as bullying, sexual violence and intolerance do not develop. From the results of this activity, it is hoped that by instilling these values, underage children can become individuals who care about others and overcome negative behavior. Apart from that, the school and the child's social environment, including parents, are expected to provide a special space for children to provide an understanding of friendship etiquette, study etiquette, as well as the negative impact of bullying and sexual violence. This socialization activity involved 50 children from pre-school, preschool, to elementary school ranging from grades 1 to grade 5, and was held on Wednesday, 02 October 2024. Keyword: 3 Sins of Education, Socialization of Education